Certain trends in uncertainty and sensitivity analysis: An overview of software tools and techniques. (February 2020) - Douglas-Smith, Dominique; Iwanaga, Takuya; Croke, Barry F.W.; Jakeman, Anthony J.
Abstract: Uncertainty and sensitivity analysis (UA/SA) aid in assessing whether model complexity is warranted and under what conditions. To support these analyses a variety of software tools have been developed to provide UA/SA methods and approaches in a more accessible manner. This paper applies a hybrid bibliometric approach using 11 625 publications sourced from the Web of Science database to identify software packages for UA/SA used within the environmental sciences and to synthesize evidence of general research trends and directions. Use of local sensitivity approaches was determined to be prevalent, although adoption of global sensitivity analysis approaches is increasing. We find that interest in uncertainty management is also increasing, particularly in improving the reliability and effectiveness of UA/SA. Although available software is typically open-source and freely available, uptake of software tools is apparently slow or their use is otherwise under-reported. Longevity is also an issue, with many of the identified software appearing to be unmaintained. Improving the general usability and accessibility of UA/SA tools may help to increase software longevity and the awareness and adoption of purpose-appropriate methods. Usability should be improved so as to lower the "cost of adoption" of incorporating the software in the modelling workflow. An overview of available software is provided to aid modelers in choosing an appropriate software tool for their purposes. Code and representative data used for this analysis can be found at https://github.com/frog7/uasa-trends (10.5281/zenodo.3406946). Highlights: A hybrid bibliometric analysis is applied to 11, 625 environmental science publications obtained through Web of Science. Identifies software for uncertainty and sensitivity analysis with an overview of the general research trends. Improving usability and accessibility of software may increase adoption and awareness of purpose-appropriate methods. Comparisons between software including the implemented analysis methods and availability are given.